Antibiotic Utilization and Its Implications Among Ruminant Farmers and Stakeholders in Sumbawa Regency, Indonesia - Nurul Jannah; null Fahrunnisa; Yudith Vega Paramitadevi; Heryudianto Vibowo; Fariz Am Kurniawan; Nurul Amri Komarudin; Aceng Hidayat (Veterinary Medicine International)
The rise in antimicrobial resistance is a vital concern, and various factors, such as the overuse of antibiotics in agriculture, have contributed to its development and spread. Livestock farmers, veterinarians, and pharmacies are key prescribers of antibiotics for disease prevention, control, and treatment of ruminant animals. A qualitative study in the Sumbawa District examined their awareness, attitudes, and practices concerning antibiotic use, residues, and resistance, underscoring their vital role in tackling this challenge. The study utilized nine key informant interviews, sixteen in-depth interviews, a single focus group discussion, and on-farm observations using semistructured formats and thematic analysis to identify and explore themes. This revealed a common practice of antibiotic self-medication among ruminant farmers in the Sumbawa Regency, driven by limited knowledge and leading to medicine store purchases based on advice from veterinary paraprofessionals or for unregulated self-treatment. Factors contributing to antibiotic misuse include trust in veterinary paraprofessionals, economic limitations, lack of targeted antiresistance programs, and insufficient regulation of antibiotic sales. Enhancing veterinary paraprofessionals' awareness of their ethical duties, launching educational programs for actors, providing financial support for these initiatives, and strict enforcement of regulations by the local government are strategies that could collectively promote responsible antibiotic use and stewardship.